Incidencia de las actividades relacionadas al Turismo Místico en la parroquia Jimbura, Cantón Espíndola, provincia de Loja - Loaiza Cumbicus, Tania Lisbeth (2023)
This research project is linked to the mystical tourism and its impact in the town of Jimbura, parish of Espíndola; it is immersed in experiential tourism on the practices and ancestral knowledge developed within the Yacurí National Park. Part of this research argues that tourism in the town is not practiced in a sustainable way, which affects the water resources of the area. Therefore, in this way three specific objectives are proposed: identify activities related to mystical tourism in Jimbura parish; measure the incidence of activities related to Mystic Tourism in the population of Jimbura and propose tourism management strategies for the parish. As part of the methodology, the INPC heritage registration and inventory matrices are adapted and applied. Thus, to meet the objectives, qualitative and quantitative methods were applied, determining two research techniques: the survey, which was addressed to 247 inhabitants of the Jimbura parish based on the Likert scale and the interview (shamans and healers and park rangers of the Yacurí National Park). In addition, experiential tourism, it allowed to learn about the ceremonial healing practices and other good luck rites. Furthermore, a high negative incidence was demonstrated in the economic (42.51%), sociocultural (40.38%) and environmental (43.80%) aspects, on the other hand, it was established that there is a medium positive incidence in the sociocultural field (38.81%) and a high positive incidence in the environmental aspect (44.77%). In the same way, it was possible to identify that the park rangers have implemented care actions around the environment. Finally, it was possible to establish tourism management strategies linked to activities related to mystical tourism, resulting in generating activities or products that incorporate cultural, rural, experiential, mystical and nature trends; Likewise, the design of awareness campaigns and inclusive awareness to promote sustainable care in protected areas and carry out conscious tourism. In addition, to include recommendations addressed to the Decentralized Autonomous Government of the Espíndola canton, the Ministry of the Environment of Ecuador and the Ministry of Tourism.